Spiritualitas Pentakosta Berdasarkan Perspektif Liturgi Katolik - Wibowo, Darren Milano; Stevani, Novia (Pusat Studi Pentakosta Indonesia, 2024)
AbstractThe Pentecostalism movement has grown so rapidly that its impact and movement is not limited to certain denominations. Even for some Catholic groups, this movement is also practiced by them. This happens because of a deep longing for the movement of the Holy Spirit. The liturgy of worship in Catholicism is considered monotonous and not passionate. So this is enough to trigger the existence of Charismatic Catholicism or what is commonly referred to as